Preparation and characterization of encapsulated burkholderia strain UPM B3. - Adzmi, Fariz; Meon, Sariah (2011)
The development of cost effective, user friendly and readily available commercial formulations for beneficial microbes has always been a constraint in sustaining the performance of the BCAs. Formulation of biological control agents for commercial use generally involves the mixing of viable BCAs cells with carrier-based materials in liquid or dry form and nutritional supplements such as glucose to develop fine formulations that not only can stabilize and enhance the growth of BCAs but also convenient for storage and user friendly for field and glasshouse applications. This study reports on the encapsulation of Burkholderia strain UPMB3 in sodium alginate (SA) as the matrix and montmorillonite (MMT) clay to improve the Viability and shelf life of the bioagent (SA-MMT). MMT is most widely known for its ability to swell. The high water absorption capacity of montmorillonite also makes it very elastic and resistant to fracturing. SA-MMT was characterized using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA) and Scanning Electron Microscopy (SEM). FTIR results showed the interaction between the functional groups of SA and MMT in the SA-MMT beads. TGA analysis showed the incorporation of MMT in SA-MMT beads increased the thermal stability of the formulations due to the high thermal stability of the MMTand to the interaction between the MMT particles and the alginate matrix. SEM analysis revealed homogeneous distribution of the MMT particles throughout the SA matrix and the smooth surface of the SA-MMT compare to SA alone. Burkholderia strain UPM B3 was successfully encapsulated in the SA-MMT beads. Storage analysis of the encapsulated Burkholderia strain UPM B3 showed that lower storage temperature of,l6 °C significantly (P<O.05) gave better storage properties compared to room temperature (30°C).